Perancangan Charger Station Dengan Pembayaran Uang Koin Beserta Analisa Potensi Bisnisnya - Rian Tedy Lestari; Djadjat Sudaradjat; Trisna Fajar Prasetyo (Jurnal Elektronika dan Teknik Informatika Terapan ( JENTIK ), 2023)
At this time, many electronic devices use battery technology such as laptops, cell phones, Bluetooth earphones (TWS), Bluetooth speakers and others. The device requires electrical energy from the battery to operate. It's normal for people with high mobility who often leave the room to run out of battery power. Because of that, how do you solve the problem of running out of battery energy / low battery on electronic devices, because of that a charger station tool was designed with coin payments where there is business potential in designing the device. This study uses the PZEM-004T module as an electrical energy sensor and multi coin acceptor to select coins that enter the charger station system, then the WeMos D1 mini will control the SSR and provide information via the 16x2 Alphanumeric LCD and the Blynk application because the WeMos D1 mini module supports the Internet. of Things (IoT). The information displayed on the Alphanumeric 16x2 LCD is the remaining kWh balance, voltage and load power of the charger station user, then the Blynk application displays information on the number of rupiah coins that have been entered, the remaining kWh balance, voltage, current, power factor and load power of the charger user. This charger station system uses a coin of Rp. 100, Rp. 200, Rp. 500 and Rp. 1000, where if the coins are inserted into the charger station system, the user will get a kWh electricity balance according to the calculation of the selling price. The author uses a profit margin of 300% of the cost of class B1 PLN electricity rates plus the cost of the charger station system electricity.